Digital Literacy for MSME Actors of Sidoarjo Food and Beverage Association (ASMAMINDA) - Sufa, Siska Armawati; Rachmanto, Tito; Adistie, Gisti Riza; Anwar, Khairil; Setyawan, Dedi (Journal of Community Service and Society Empowerment, 2024)
This study aims to investigate the importance of digital literacy in increasing the market competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Sidoarjo Food and Beverage Association (ASMAMINDA). Using qualitative methods and case studies, this research provides insight into how to overcome obstacles that hinder sustainable economic growth and the long-term survival of MSMEs in the digital era. The results show that although digital opportunities exist, the adoption of digital skills among ASMAMINDA MSMEs is still low. The results demonstrate that digital literacy is not only a vital skill set enabling MSME participants to proficiently navigate the digital marketplace, but also a potent instrument for leveraging technological advancements to drive economic growth and sustainability in Sidoarjo District, renowned for its diverse economic activities and entrepreneurial vitality. This research offers a new perspective in the discussion on digital literacy and the application of digital technology in the local scope of MSMEs.